Clinical Characterization of Symptomatic Microangiopathic Brain Lesions - Leistner, Stefanie; Koennecke, Christian; Dreier, Jens P.; Strempel, Anne K.; Kathke, Markus; Nikolova, Alexandrina; Heuschmann, Peter; Malzahn, Uwe; Audebert, Heinrich J.; Mackert, Bruno M. (Frontiers in Neurology, 2011)
Background: Microangiopathic brain lesions can be separated in diffuse lesions - leukoaraiosis - and focal lesions - lacunes. Leukoaraiosis and lacunes are caused by common cerebrovascular risk factors, but whether they represent a common entity is not sufficiently investigated. The present study aimed to determine the clinical profiles associated with the extent of leukoaraiosis and lacunes. Methods: 64 consecutive patients with acute microangiopathic stroke were studied. Leukoaraiosis and lacunes were stratified according to their MRI-based extent. Standardized clinical assessment included clinical syndromes, cerebrovascular risk factors, cognitive performance, retinal imaging, ultrasonography, blood and urine parameters. Results: Different clinical profiles for leukoaraiosis and lacunes were found. Regarding leukoaraiosis, the cognitive scores (SISCO, MMSE, ME) and the presence of hyperlipidemia decreased as the severity of leukoaraiosis increased. Univariate and multivariate analysis revealed that these cognitive score values as well as the presence of hyperlipidemia correlated significantly with no or only mild leukoaraiosis. Regarding lacunes, the percentage of migraine, previous stroke events, hydrocephalus, left ventricular hypertrophy and a higher NIHSS increased as the number of lacunar lesions increased. Statistical analysis revealed that these parameters correlated not significantly with the number of lacunes. Conclusions: The findings suggests that leukoaraiosis and lacunes are different microangiopathic entities potentially requiering different treatment concepts.